Electrodeposition of Tin Selenide from Oxalate-Based Aqueous Solution. Issue 16 (30th November 2020) - De Vos, Mélanie; Danine, Abdelaadim; Adam, Laura; Diliberto, Sébastien; Caballero-Calero, Olga; Martín-González, Marisol; Péter, László; Csík, Attila; Kálmán, Vad; Philippe, Laetitia; Osenberg, David; Al-Alam, Patricia; et al.
Abstract : In this work, we report a study of the electrodeposition of SnSe. Considering the difficulty to stabilize the baths containing Sn(II) and Se(IV) precursors, we investigated the benefits of using sodium oxalate as a complexing agent. Preliminary cyclic voltammetric (CVs) experiments were performed to study the electrochemical behavior of tin and selenium redox systems within this specific electrolyte solution. The study revealed that the oxalate reagent stabilizes the bath chelating Sn(II) and then preventing the precipitation of SnO2 . From the CVs, a growth mechanism is proposed and a synthesis potential window is defined, in which the electrodeposition of SnSe films was investigated. Between −0.5 and −0.6 V vs sat. AgCl/Ag, the deposits exhibit typical polycrystalline SnSe needle-like grains. SnSe was shown by Raman spectroscopy and the XRD patterns display an orthorhombic single-phase for this compound. Additional Mössbauer analyses confirm the presence of Sn(II), which is in good agreement with the chemical composition of SnSe films. Moreover, a cross-analysis between the methods shows also the presence of SnSe2 in minor proportion. The depth profile analyses of the samples reveal an in-depth homogeneity as well as the presence of oxygen at the layer surface.